Suboptimal extracellular pH values alter DNA damage response to induced double‐strand breaks - Julien Massonneau; Camille Ouellet; Fabrice Lucien; Claire M. Dubois; Jessica Tyler; Guylain Boissonneault (FEBS Open Bio)
Conditions leading to unrepaired DNA double‐stranded breaks are potent inducers of genetic instability. Systemic conditions may lead to fluctuation of hydrogen ions in the cellular microenvironment, and we show that small variations in extracellular pH, termed suboptimal pHe, can decrease the efficiency of DNA repair in the absence of intracellular pH variation. Recovery from bleomycin‐induced DNA double‐stranded breaks in fibroblasts proceeded less efficiently at suboptimal pHe values ranging from 7.2 to 6.9, as shown by the persistence of repair foci, reduction of H4K16 acetylation, and chromosomal instability, while senescence or apoptosis remained undetected. By allowing escape from these protective mechanisms, suboptimal pHe may therefore enhance the genotoxicity of double‐stranded breaks, leading to genetic instability.